2018
DOI: 10.1158/1078-0432.ccr-18-0133
|View full text |Cite
|
Sign up to set email alerts
|

The Light Chain IgLV3-21 Defines a New Poor Prognostic Subgroup in Chronic Lymphocytic Leukemia: Results of a Multicenter Study

Abstract: Unmutated (UM) immunoglobulin heavy chain variable region (IgHV) status or IgHV3-21 gene usage is associated with poor prognosis in chronic lymphocytic leukemia (CLL) patients. Interestingly, IgHV3-21 is often co-expressed with light chain IgLV3-21, which is potentially able to trigger cell-autonomous BCR-mediated signaling. However, this light chain has never been characterized independently of the heavy chain IgHV3-21. We performed total RNA sequencing in 32 patients and investigated IgLV3-21 prognostic impa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 38 publications
5
39
0
Order By: Relevance
“…Therefore, the total IGLV3-21 frequency in AC III was only 8.89%, but the IGLV3-21 R110 CLL cases were distributed through M-CLL (3 cases) and UM-CLL (4 cases) classification (SI Appendix, Fig. S4) (18,28). Similarly, different IGHV genes were found to be effectively pairing with the IGLV3-21 R110 LC and only 2 of the 7 IGLV3-21 R110 cases were annotated as conventional subset 2, confirming again that subset 2 represents only a minor subgroup of IGLV3-21 R110 -expressing CLL (SI Appendix, Table S10).…”
Section: Iglv3-21 and Iglv3-21 R110 Clls Are Uniform By Single-cell Smentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the total IGLV3-21 frequency in AC III was only 8.89%, but the IGLV3-21 R110 CLL cases were distributed through M-CLL (3 cases) and UM-CLL (4 cases) classification (SI Appendix, Fig. S4) (18,28). Similarly, different IGHV genes were found to be effectively pairing with the IGLV3-21 R110 LC and only 2 of the 7 IGLV3-21 R110 cases were annotated as conventional subset 2, confirming again that subset 2 represents only a minor subgroup of IGLV3-21 R110 -expressing CLL (SI Appendix, Table S10).…”
Section: Iglv3-21 and Iglv3-21 R110 Clls Are Uniform By Single-cell Smentioning
confidence: 99%
“…Fig. 1C and D)(13,18,20). Several other IGHV genes were found to be effectively pairing with the IGLV3-21 LC (SI Appendix,Table S2), indicating that CLL subset 2 represents a minor subgroup of IGLV3-21R110 expressing CLL, while the majority have hitherto not been recognized as an immunobiologically related CLL subset.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 This change is present in 7-18% of CLL and seems responsible for the adverse outcome associated with the use of IGLV3-21 independently of the mutational status of the IGHV. 24,25 Epigenetic studies have shown that, although both CLL subtypes are antigen-experienced, M-CLL keeps a methylation signature of germinal center-experienced cells (memory-like B cells), whereas U-CLL has a pre-germinal center, naïve-like methylation signature .5,26 Of note, these epigenetic studies also identified a third subtype with an intermediate profile made of cases with moderate IGHV mutation levels. All three epigenetic subsets have different usage of IGHV genes, stereotypes, genomic aberrations and clinical outcome ( Table 1).…”
Section: Cell Of Originmentioning
confidence: 99%
“…Our study cohort was recruited from our own CLL database, and was selected by the presence of TP53 mutations and del17p13.1. The 11 samples included both mutated (n=5) and unmutated (n=6) IgHV genes (including three cases with two rearrangements each), seven mutations in TP53 (five missense, one stop gain and one frameshift deletion) and four del17p13.1events (table 1), previously identified through at least one of either short-read whole genome sequencing 23 (WGS), whole transcriptome sequencing 23,24 (WTS), targeted deep-sequencing 25 or Sanger sequencing 24 . Genomic DNA was extracted from peripheral blood samples of the 12 untreated CLL patients using a Qiagen DNA Blood mini kit (Qiagen, Hilden, Germany).…”
Section: Sample Selection and Dna Extractionmentioning
confidence: 99%